Depressive symptoms and smoking among young Turkish and Moroccan ethnic minority groups in the Netherlands: a cross-sectional study - Agyemang Charles; Nierkens Vera; Acartürk Ceren Z; Stronks Karien (BMC, 2011)
Abstract Background Although evidence indicates a strong association between depressive symptoms and smoking among host and migrant adults, less is known about this relationship among young ethnic minority groups in Europe. This paper aims to assess the relationship between depressive symptoms and smoking among young Turkish and Moroccan migrants in the Netherlands. Methods Multiple logistic regression analyses was used to analyze cross-sectional data from a sample of 364 Turkish and Moroccan migrants aged 15 to 24 years. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure the presence of clinically significant depressive symptoms. Smoking behavior was measured by a number of questions. Results Of the respondents, 22% were smokers and 33% had depressive symptoms. The prevalence of depressive symptoms was significantly higher in smokers (42.9%) than in nonsmokers (29.5%). Respondents with depressive symptoms had increased odds of smoking even after adjusting for socioeconomic and cultural factors (OR = 2.68, 95% CI = 1.45-4.97). Conclusions Depressive symptoms were significantly associated with smoking behavior in young Turkish and Moroccan migrants. In addition to other acknowledged factors, depressive symptoms should also be considered in relation to the smoking behavior of this group. Intervention programs for smoking behavior should take depressive symptoms into account for young Turkish and Moroccan migrants.